Work-related injury characterization and factors among fire brigade workers in Ethiopia - Eshetu Abera Worede; Kedir Yesuf; Lidetu Demoze; Gelila Yitageasu; Bikes Destaw Bitew (Scientific Reports)
Abstract Fire brigade workers face numerous occupational hazards, including exposure to fire, hazardous materials, and strenuous physical activities. In Ethiopia, the prevalence of work-related injuries and associated factors among fire brigade workers is not well documented. This study aimed to assess these among fire brigade workers in Ethiopia in 2024. An institutional-based cross-sectional study was conducted from June to August 2024. A simple random sampling technique was used to select 420 participants. Data were collected through face-to-face interviews using a structured questionnaire. SPSS version 26 was used for data analysis. Bivariable and multivariable regression analyses were conducted to identify factors associated with injuries. A total of 420 participants with a response rate of 99.5% participated in the study. The annual prevalence of work-related injuries was 38.3% (95% CI: 33.7–43.2). The upper extremity (11.1%) was the most injured body region, followed by the lower extremity (9.9%) and back (6%). Fractures/dislocations (8.1%), burns (7.9%), and wounds (6.7%) were common types of injuries reported. Income, alcohol consumption, poor health and safety conditions, operating using machinery, using a mobile device to transport materials, and failure to maintain equipment promptly were significantly associated with work-related injuries among firefighters. The prevalence of work-related injuries among fire brigade workers is high. Monthly income, poor health and safety conditions, operating using machinery, using mobile devices for material transport, delays in equipment maintenance, and alcohol consumption are significant factors for injuries. Continuous training on occupational health and safety, risk awareness, and injury prevention should be provided to all employees.